DESIGNING COMMUNICATIVE AND NEEDS-BASED ENGLISH TEACHING MATERIALS THROUGH TRAINING AND MENTORING - Kartin Lihawa (Journal of Community Services on Multidisciplinary Sciences, 2026)
This community service program aimed to design communicative and needs-based English teaching materials through training and mentoring activities for junior high school English teachers. The program was conducted in response to problems in English teaching, particularly the limited use of communicative learning methods, teachers’ dependence on grammar-focused instruction, limited teaching materials, and students’ low motivation and English achievement. The objective of the program was to improve teachers’ knowledge and skills in developing learner centered and contextual English teaching materials based on needs analysis. The program applied a participatory approach through workshops, group discussions, hands-on practice, and continuous mentoring sessions. Participants were introduced to communicative language teaching principles, needs analysis techniques, and strategies for designing interactive learning materials. The mentoring process also assisted teachers in revising and implementing the materials in classroom practice. As a result, participants demonstrated improved understanding, creativity, confidence, and competence in developing relevant, interactive, and communicative English teaching materials.